Analisis Faktor Asi Ekslusif pada Resiko Kejadian Stunting pada Anak Usia 2 – 24 Bulan di Desa Matang Maneh, Kec. Tanah Jambo Aye, Kab. Aceh Utara 2024 - Futry Maysura; Wahyuni Wahyuni (Pusat riset dan Inovasi Nasional, 2025)
Stunting is a chronic nutrition problem that affects the growth and development of children. This study aims to analyze the relationship between exclusive breastfeeding and the incidence of stunting in children aged 2-24 months in Matang Maneh Village. The research used a quantitative approach with a survey method. Data were collected through structured questionnaires, and the relationship was analyzed using the chi-square test. The results showed a Pearson Chi-Square value of 5.185 with a significance level of 0.023 (p < 0.05). This indicates a significant relationship between exclusive breastfeeding and stunting. Children who did not receive exclusive breastfeeding had a higher risk of stunting compared to those who did. This study highlights the importance of exclusive breastfeeding in preventing stunting. These findings can serve as a basis for creating intervention programs to increase exclusive breastfeeding coverage and reduce stunting prevalence, especially in Matang Maneh Village.